Effect of improving Fe2B toughness by chromium addition on the two-body abrasive wear behavior of Fe–3.0 wt% B cast alloy. (September 2016) - Jian, Yongxin; Huang, Zhifu; Xing, Jiandong; Zheng, Baochao; Sun, Liang; Liu, Yangzhen; Liu, Yanmei
Abstract: Effects of chromium addition on microstructure, two-body abrasive wear behavior of Fe–B cast alloy and fracture toughness of boride were investigated. The results indicate the solidification microstructure of Fe–3.0 wt% B alloy consists of ferrite, pearlite and eutectic boride. After quenching, the alloy microstructure is composed of martensite and boride. With Cr addition increasing, microhardness of matrix and boride has tiny fluctuation; fracture toughness of M2 B increases first reaching the maximum (4.704 MPa m 1/2 ) at 2.0 wt% and then decreases; two-body wear resistance increases first and then decreases under contact loads of 15 N, 35 N and 55 N, possessing similar variation trend with fracture toughness of M2 B. This indicates the toughness of M2 B has directly positive influence on wear resistance of Fe–3.0 wt% B cast alloy. Highlights: With Cr addition increasing, fracture toughness of boride increases first and then decreases. Wear resistance of Fe–3.0 wt% B cast alloy increases first and then decreases slightly with increasing Cr addition. Both toughness of boride and wear resistance of the alloy obtain maximum value at Cr addition of 2.0 wt%. Toughness of boride has direct influence on wear resistance of the alloy.